Encyclopedia of environmental change - Matthews, John A. (John Anthony), 1947- (Thousand Oaks, California : SAGE Publications, 2014)
Accessibly written by a team of international authors, the Encyclopedia of Environmental Change provides a gateway to the complex facts, concepts, techniques, methodology and philosophy of environmental change. Over 4,000 entries explore the following key themes and more: conservation; demographic change; environmental management; environmental policy; environmental security; food security; glaciation; the green revolution; and human impact on the environment.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 15, 2014).
Keywords: Global environmental change -- Encyclopedias